Increasing Production Capacity by Designing Facilities to Reduce Production Costs: Peningkatan Kapasitas Produksi dengan Melakukan Perancangan Fasilitas Guna Menurunkan Biaya Produksi - Yudi, Masyudi; Hery, Hery Murnawan (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2023)
This research discusses facility design in the lightweight brick manufacturing industry. Every year the production costs of making lightweight bricks continue to increase due to increases in raw material prices, increases in minimum wages and increases in several auxiliary materials. The increase in selling prices cannot offset the increase in production costs because price competition in the market is high. This research aims to plan to increase the production capacity of lightweight bricks from initially 679.4m³ per day to 794.7m³ per day by designing facilities at lightweight brick manufacturing companies. This research also calculated how much it costs to produce lightweight bricks before designing, namely with a capacity of 679.4 m³ per day and how much it costs to produce lightweight bricks after designing the facilities, namely 794.7 m³ per day. The results of this research are in the form of production capacity data from each production work floor, as well as production work floors where facilities were designed so that a production capacity of 794.7 m³ per day could be achieved. And also calculate how much production costs will be with a production capacity of 679.4m³ and 794.7m³ per day.